Adsorptive recovery of high value essential oil from kewda (Pandanus fascicularis Lam) distillation condensate. Issue 5 (28th April 2015) - Rout, Prasant Kumar; Rao, Y. Ramachandra; Prakash, Om; Khare, Puja
Abstract Kewda (Pandanus fascicularis Lam) essential oil was enriched with phenylethyl methyl ether (65–77%), terpinen‐4‐ol (13–18%) and α‐terpineol (1–3%), which were definitely soluble in distillation condensate. The solubility of phenylethyl methyl ether, terpinen‐4‐ol and α‐terpineol in water were more than 1000 ppm. Adsorption performance of single‐solutes and multi‐solutes over Amberlite‐resins and Indion‐resins were elucidated. XAD‐4 and Indion 1014 MN‐2 were most suitable because of their higher loading capacities of 2.2–3.2 mmol g−1 and 2.3–3.6 mmol g−1, respectively. Temkin adsorption isotherm was best fitted to the experimental results. Adsorption was followed Pseudo‐second order, Ritche's‐second order and Elovich's equation to validate the kinetics of chemisorption. Column breakthrough results revealed that the water soluble essential oil was recovered from the distillation condensate through a resin bed. Then the adsorbed solutes were desorbed from the resins with elution in ethanol to achieve complete recovery of high value essential oil from the distillation condensate. © 2015 Curtin University of Technology and John Wiley & Sons, Ltd.